The impact of corporate governance and compliance control on the continuity of banks in Iraq (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research aims to clarify the concept of corporate governance, its importance, objectives, internal and external mechanisms, as well as a statement of the concept and objectives of compliance control as well as the basic principles of compliance control in addition to the characteristics of the compliance controller, as well as a statement of the concept of continuity and identification of indicators of continuity doubt. As a main tool in collecting data from the research sample of (70) people, as well as analyzing the data based on the ready-made statistical program (spss) in calculating the arithmetic mean and standard deviation, correlation coefficient, simple linear regression, as well as the (F) test. The researcher reached a set of conclusions, the most important of which is that the proper application of corporate governance rules and mechanisms, whether internal or external, is vital and important to monitor managers and reduce conflicts of interest and works to reduce problems and leads to attracting capital and optimal utilization of available resources. Compliance helps in assessing and controlling the risks of non-compliance through the vital control and supervisory role And the independent compliance controller in order to face the risks to which the bank is exposed, and in the light of the conclusions, the researcher reached a set of recommendations, the most important of which is the need to seek to enhance the application of aspects of corporate governance effectively and efficiently to protect the economic unit from crises and future risks, as well as working on the need to benefit from the outputs of the Basel Committee Concerning compliance control for the purpose of strengthening internal audit in the event of weakness or deficiencies in the performance of internal audit and emphasizing the importance of adherence to the principles of compliance control and the need to support the independence of the compliance controller by the Board of Directors in order to raise the ability and level of professional performance of the compliance controller, which effectively contributes to enhancing continuity Unit .